Penerapan Konsep Model Altman Z-Score Modifikasi dalam Menilai Kualitas Laporan Keuangan Perusahaan PT Wijaya Karya (Persero) Tbk (WIKA) - Nurul Hilmi; Muhammad Rusydi; Masrullah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Corporate financial health constitutes a crucial indicator of business sustainability, particularly in construction companies that face liquidity pressures and substantial financing requirements. An assessment of the financial condition of PT Wijaya Karya (Persero) Tbk during the 2022–2024 period was conducted using the Modified Altman Z-Score model to identify its financial health status and the likelihood of financial distress. This research employed a descriptive quantitative approach based on secondary data derived from the company’s annual financial statements. The findings reveal that the company consistently remained within the financial distress category throughout the observation period, as its Z-Score values continuously fell below the critical danger-zone threshold. The financial trajectory exhibited a U-shaped pattern, beginning with a fragile early-warning phase before deteriorating sharply into negative territory due to working capital deficits and substantial operating losses. Signs of improvement emerged in the final year of observation, supported by enhanced liquidity resulting from the successful restructuring of short-term liabilities. Nevertheless, a complete recovery has yet to be achieved because of the expanding retained earnings deficit generated by accumulated historical losses. These findings underscore the importance of fundamental restructuring measures and stronger capital management strategies to ensure the company’s long-term financial sustainability.